2022
DOI: 10.1086/711834
|View full text |Cite
|
Sign up to set email alerts
|

Political Ideology and the Perceived Impact of Coronavirus Prevention Behaviors for the Self and Others

Abstract: At the time of this writing, COVID-19 has spread rapidly worldwide. Even though the United States became the epicenter of the pandemic in April 2020, partisan differences have been observed in terms of willingness to engage in coronavirus-prevention behaviors. Across four studies and an exploratory pilot study, we demonstrate that conservatives differ from liberals in their perceptions of preventive behaviors. Conservatives view preventative actions as being less impactful on others, which is partially due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 32 publications
0
30
1
1
Order By: Relevance
“…This internalization can then cause people to feel greater freedom because they value following restrictions enough that they would choose to do so even without external mandates (Deci et al, 1994;Moller et al, 2006). In line with previous work on the value of understanding, initial research in the context of the COVID-19 pandemic has found that people who perceive preventative measures as more effective are more likely to adhere to government guidelines like wearing masks (Broomell et al, 2020;Cakanlar et al, 2021;Clark et al, 2020;Sprengholz et al, 2020). Moreover, providing information about the benefits behind pandemic policies reduced reactance in the face of restricted freedom (Sprengholz et al, 2020).…”
Section: Principle 1: Spell Out Benefits Of Restricted Freedom/increased Securitymentioning
confidence: 78%
“…This internalization can then cause people to feel greater freedom because they value following restrictions enough that they would choose to do so even without external mandates (Deci et al, 1994;Moller et al, 2006). In line with previous work on the value of understanding, initial research in the context of the COVID-19 pandemic has found that people who perceive preventative measures as more effective are more likely to adhere to government guidelines like wearing masks (Broomell et al, 2020;Cakanlar et al, 2021;Clark et al, 2020;Sprengholz et al, 2020). Moreover, providing information about the benefits behind pandemic policies reduced reactance in the face of restricted freedom (Sprengholz et al, 2020).…”
Section: Principle 1: Spell Out Benefits Of Restricted Freedom/increased Securitymentioning
confidence: 78%
“…However, the results of Study 1 demonstrate that factual information is not the only consideration driving subjects' attitudes about the COVID-19 vaccine. Recent studies indicate that individuals' political ideology strongly influences their perceptions and acceptance of risk (Cakanlar et al,. 2020;Nowlan and Zane, 2020;Roozenbeek et al, 2020;Van der Linden et al, 2020), making it of particular importance in determining vaccine attitudes.…”
Section: Study 1 Discussionmentioning
confidence: 99%
“…In their examination of the role of political ideology in consumer reaction to multiple consumption regulations (e-cigarettes, food warning labels, and using mobile phones while driving), Irmack and others (2020) found that the position held by the political party that subjects support affects how they cognitively and affectively process information presented to them about an issue. Moreover, numerous studies demonstrate that political ideology is a key contributor to individuals' attitudes about the level of threat attributed to the COVID-19 virus (Cakanlar et al, 2020;Kelly et al, 2020;Nowlan and Zane 2020;Roozenbeek et al, 2020;Van der Linden et al, 2020), as well as the efficacy of the vaccine (Bechler and Tormala, 2020;Chou and Budenz, 2020;Tyson et al, 2020).…”
Section: Political Ideologymentioning
confidence: 99%
See 2 more Smart Citations